1987
DOI: 10.3109/10641968709160030
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Sympathetic Constriction of the Ex Vivo Tail Artery Perfused with Blood from Rats Given Frusemide

Abstract: Blood was withdrawn at a constant rate from the cannulated carotid artery of an anaesthetized rat and perfused an ex vivo segment of tail artery cannulated at both ends and contained in an organ bath. Blood returned to the rat via a cannulated jugular vein. The tail artery was constricted and perfusion pressure increased by peri-arterial stimulation at 5 Hz for 5 s every 2 min. Intravenous frusemide (5 mg/kg) decreased the stimulation responses of the tail artery. Diuresis-induced volume losses after frusemide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This effect is also inhibited by blockade of prostanoid synthesis and requires the kidneys and an intact vascular endothelium (Gerkens 1987;Gerkens et al 1987a, b). The effect of frusemide on the response to sympathetic nerve stimulation is also abolished by the angiotensin I1 receptor blocker saralasin (Gerkens et al 1987b). Frusemide, by stimulating the renal production of prostanoids (Scherer and Weber 1979), activates the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is also inhibited by blockade of prostanoid synthesis and requires the kidneys and an intact vascular endothelium (Gerkens 1987;Gerkens et al 1987a, b). The effect of frusemide on the response to sympathetic nerve stimulation is also abolished by the angiotensin I1 receptor blocker saralasin (Gerkens et al 1987b). Frusemide, by stimulating the renal production of prostanoids (Scherer and Weber 1979), activates the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…Frusemide, by stimulating the renal production of prostanoids (Scherer and Weber 1979), activates the renin-angiotensin system. Angiotensin I1 probably acts on the kidneys to release a yet unknown substance that interacts with endothelium to cause vasodilatation (Gerkens et al 1987b). Chemical renal medullectomy has demonstrated that this unknown vasodilator is produced in the renal medulla and may be a lipid (Gerkens et al 1987a).…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been described previously (Gerkens et al 1987). Rats were anaesthetized and the trachea, carotid artery, both jugular veins and the urinary bladder cannulated.…”
Section: Rat Ex Vivo Blood Perfused Tail Arterymentioning
confidence: 99%
“…It has been reported that furosemide was able to reduce blood pressure prior to inducing a significant diuretic effect ( Dikshit et al ., 1973 ). From experiments performed in vivo and ex vivo in rats, it has been proposed that the final antivasoconstrictor effect of furosemide requires an intact vascular endothelium ( Gerkens et al ., 1987 ; 1988 ). More recently, furosemide has been shown to increase the release of prostacyclin, together with endothelial kinins and NO, from primary cultured bovine aortic endothelial cells ( Wiemer et al ., 1994 ).…”
Section: Introductionmentioning
confidence: 99%